COMPARISON THE SUCCESS RATE OF VESICOVAGINAL FISTULA REPAIR SURGICAL WITH TRANSVAGINAL AND TRANSABDOMINAL PROCEDURE : META ANALYSIS - Norma Pattinama; Gatut Hardianto (UNUSA Press, 2020)
Objective: This paper aims to evaluate the success rate of vesicovaginal fistula (VVF) repair surgery by transvaginal (TVAG) and transabdominal (TPA) procedure. Method: Literatures were searched on the online database, PUBMED and Google Scholar. All of the studies should be belonging on to inclusion criteria. The literatures had qualitative analyze by the authors and bias criteria based on Review Manager 5.3 application. It also had quantitative analyzed by the same application. Results: The literatures have 191 patients (transvaginal-n=107; transabdominal-n=84). The data was homogen (Chi2<df; P>0,05). The forest plot showed that TPA has a higher success rate than TVAG, still not statistically significant (test overall effect P>0,05; 95%CI was 0,59 to 5,30). Conclusion: Transabdominal procedure has a higher success rate.